Profil Empati Mahasiswa Universitas Mathla’ul Anwar Banten - Amelia Ayu Pratiwi; Mila Rosmila; Ade Hidayat (Indonesian Journal of Educational Counseling, 2019)
EMPATHY PROFILE OF UNIVERSITAS MATHLA’UL ANWAR BANTEN STUDENTS. This study aims to reveal the empathy of Universitas Mathla’ul Anwar Banten students. The method used in this research is descriptive with the type of survey. The population of this study was students of Mathla'ul Anwar Banten University. The validity test of the research instrument items was carried out with the Product Moment correlation formula. The results of the validity test of 20 items resulted in 17 valid items and 3 drop items. Invalid statement items are changed and the editor corrects them to become new statements. The reliability test with the Cronbach Alpha formula obtained research results 0.803, which means that the instrument has a very high level of reliability. The results showed that the level of student empathy was high (64.18%), moderate (35.82%), and low (0%). The results of this study indicate that Mathla'ul Anwar University students have a high level of empathy. This is indicated by the more dominant results obtained in the medium category (64.18%). Research recommendations are shown to guidance and counseling students to improve empathy. Most of the students' empathy is still at a high level. However, there are still students who have moderate empathy so that this research can be used as the basis for developing the empathy ability of each student.